2023
DOI: 10.1039/d3fo01101a
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between mushroom consumption and cognitive performance among middle-aged and older adults: a cross-sectional study

Abstract: Background/Objectives: Bioactive compounds in mushrooms may protect the brain from neurodegeneration by inhibiting the production of amyloid-β and playing an antioxidant role. This study aimed to examine the associations of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 40 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Essential bioactives in mushrooms with hypotensive effects include ergosterol, lovastatin, cordycepin, tocopherols, chitosan, ergothioneine, γ-aminobutyric acid, quercetin, and eritadenine [73]. Consuming more mushrooms was found to be positively correlated with enhanced cognitive performance and decreased risk of mild cognitive impairment in middle-aged and older adults [74]. In addition to their antioxidant properties and ability to prevent the synthesis of amyloid-β, bioactive chemicals found in mushrooms may shield the brain from neurodegeneration.…”
Section: Mushrooms Prevent Various Nutritional Disordersmentioning
confidence: 99%
“…Essential bioactives in mushrooms with hypotensive effects include ergosterol, lovastatin, cordycepin, tocopherols, chitosan, ergothioneine, γ-aminobutyric acid, quercetin, and eritadenine [73]. Consuming more mushrooms was found to be positively correlated with enhanced cognitive performance and decreased risk of mild cognitive impairment in middle-aged and older adults [74]. In addition to their antioxidant properties and ability to prevent the synthesis of amyloid-β, bioactive chemicals found in mushrooms may shield the brain from neurodegeneration.…”
Section: Mushrooms Prevent Various Nutritional Disordersmentioning
confidence: 99%
“…8,9 Studies have reported that consuming mushrooms rich in ergothioneine can improve cognitive function. 10 An increase in mushroom consumption of 10 grams per day was associated with a 12% lower risk of MCI, 11 and consuming more mushrooms was positively associated with better cognitive function. A study on the association between mushroom intake and cognitive function in older adults in the United States suggests that higher mushroom intake may reduce the risk of cognitive decline in older adults.…”
Section: Introductionmentioning
confidence: 99%